2000
DOI: 10.1103/physrevlett.85.3938
|View full text |Cite
|
Sign up to set email alerts
|

Resonances, Instabilities, and Structure Selection of Driven Josephson Lattice in Layered Superconductors

Abstract: We investigate dynamics of Josephson vortex lattice in layered high Tc superconductors at high magnetic fields. It is shown that the average electric current depends on the lattice structure and is resonantly enhanced when the Josephson frequency matches the frequency of the plasma mode. We find the stability regions of moving lattice. It is shown that a specific lattice structure at given velocity is uniquely selected by the boundary conditions: at small velocities periodic triangular lattice is stable and lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 19 publications
2
50
1
Order By: Relevance
“…This instability corresponds to experimentally observed end point of the first flux-flow branch. It was also shown that interaction with top and bottom surfaces leads to significant lattice deformations [41].…”
Section: Solutions For the Phase Difference And The Radiation Power Amentioning
confidence: 99%
See 3 more Smart Citations
“…This instability corresponds to experimentally observed end point of the first flux-flow branch. It was also shown that interaction with top and bottom surfaces leads to significant lattice deformations [41].…”
Section: Solutions For the Phase Difference And The Radiation Power Amentioning
confidence: 99%
“…Lattice structures and their stability in this regime in the case of large lateral size l have been addressed in Ref. [41] and have been reconsidered in Ref. [42] with the conclusion that for parameters typical for BSCCO no stable regular lattice exists at high velocities.…”
Section: Solutions For the Phase Difference And The Radiation Power Amentioning
confidence: 99%
See 2 more Smart Citations
“…In this high-field region, JVs configurations in the static state are well understood and are known to be in a triangular lattice [2,3,4,5]. Despite much interest, however, dynamic state of JVs is far less understood although various aspects of dynamical properties are proposed including the possible lattice structures [6,7,8], interaction between JVs and electromagnetic excitations [9,10,11,12], and coherent characters of the JV motion [13] over the whole junctions in a stack.Key elements governing the dynamics of JVs are well reflected in the tunneling current-voltage (I-V) characteristics, which reveal the relation between the driving force acting on JVs in a junction by the bias current and the responsive JVs motion that induces a voltage drop across the junctions. For instance, JV viscosity is determined by the in-and out-of-plane quasiparticle dissipation that is extracted from the tunneling JV-flow resistance [14,15].…”
mentioning
confidence: 99%